Exploring AAC graphic symbol choices: a preliminary study - Pampoulou, Eliada; Fuller, Donald R. (My University, 2020)
Purpose: Graphic symbols have been used widely in the field of augmentative and alternative communication (AAC). The advancement of technology in recent years has stimulated their development even further, thereby providing speech-language pathologists (SLPs) a wide range of options to choose for the individuals they support. However, existing literature on graphic symbols is scant and clinicians must base their decisions almost solely on clinical judgment. This paper aims to investigate the factors SLPs consider when choosing corpuses of graphic symbols for their clients. Design/methodology/approach: An online survey was used that allowed multiple-choice responses. Data were analyzed and presented primarily as percentages. Findings: Most respondents used graphic symbols with people having developmental disorders, and the corpuses of symbols they drew upon were based predominantly on availability, characteristics of the individual’s impairment or disability and intelligibility to the user and his or her communication partners. Existing policies related to graphic symbols also influence clinicians’ choices. SLPs search for support mainly from professional associations and training providers. In terms of use with technology, ready-made symbol packages for clinicians to use were found to be attractive. Practical implications: Professional associations and institutions that focus on AAC need to provide adequate support to clinicians with a foundation based on evidence-based practice. Originality/value: To the best of the authors’ knowledge, this is the first research that focuses on current practices concerning the factors SLPs take into consideration when choosing the optimum graphic symbol corpus(es) for their clients.
Keywords: AAC; Aided symbols; Augmentative and alternative communication; Graphic symbols; Speech-language pathology